Caracterização microestrutural do aço inoxidável superdúplex UNS S32520 (UR 52N+) processado por moagem de alta energia - Yonekubo, Ariane Emi (2010)
Superduplex stainless steels are often used in applications where is necessary high mechanical strength combined with corrosion resistance. They are formed by a ferrite (a) BCC and austenite (g) FCC mixture, have a yield stress about of the double of the austenitic and ferritic stainless steels, larger plasticity that the one of the martensitic and precipitation hardening, high resistance to the intergranular corrosion, pitting and the stress-corrosion cracking. However, during hot deformation, these steels recrystallize forming a lamellar microstructure with anisotropic properties. Through the high energy milling, accomplished with Spex, Attritor and Planetary ball mills, it was aimed to obtain a homogeneous and with fine grains superduplex stainless steel. Initially, in this work, chips were made by machining of a UR 52N+ (UNS S32520) commercial superduplex stainless steel rolled sheet, without previous heat treatment, which will be submitted to the high energy milling adjusting the milling parameters and subsequently it was accomplished the heat treatment at temperatures of 1200 °C e 1250 °C for 1 hour in argon atmosphere and 1200 °C for 1 hour in argon with 2% of hydrogen. The obtained powders were analyzed by scanning electron microscopy, observing that the smaller and more homogeneous particles were obtained by Spex milling for 16 and 32 hour; the compressibility curve showed that after a long time milling, the material can present compaction difficulty and this way, great final porosity. The x ray diffraction presented peaks with a bottom widening due to the small size of the obtained particles. The porosity percentage determined by optical microscopy, reduced after heat treatment at 1200 °C in argon atmosphere with 2% hydrogen, however the scanning electron microscopy showed a fine porosity that could not be observed only in the optical microscopy analysis. The differential scanning calorimetry and the differential thermal analysis showed formation and revertion of strain induced martensite peaks and using atomic force microscopy, magnetic ferrite and paramagnetic austenite phases were observed by a non destructive test. The milling of the chips in Spex milling for 16 hours provided a refined microstructure with equiaxial grains and size of 11 μm after heat treatment at 1200 °C for 1 hour in argon atmosphere.